Study of the relationship between estrogen, leptin and TNF-alpha in low fertility women in Iraq - Hameed, Zahraa Ch (Technium BioChemMed, 2025)
fertility is one of the problems facing women and men. Estrogen (E2), leptin level disorders, and tumor necrosis factor –α (TNF-α) are among the risk factors that cause infertility. The aim of the research is to study the relationship between the three criteria and their relationship to infertility or low fertility in Iraqi women in compared with fertile women (control). The current study included (120) Participating, divided into two groups. The first group (60) infertile women) who visit outpatient infertility clinics, and (60) fertile women). The study samples were collected from September 2023 to December 2024 from outpatient infertility clinics in Iraq. All participants were between the ages of (22-38) years. The Results showed that leptin and tumor necrosis factor –α levels increased significantly in infertile women compared to fertile women in the luteal phase of the menstrual cycle, while estrogen levels decreased significantly. The conclusion: TNF-alpha, estrogen (E2), and leptin levels may be biomarkers for decreased fertility in women and may be helpful in identifying those who are at a high risk of low fertility